Mengangkat Nilai Qur’ani dalam Literasi Anak : Kreatifafa sebagai Inovasi Santripreneur di Era Digital (Studi QS. al-‘Alaq [96]: 1–5) - Lintang Dewi Fi’liya Putri; Dika Purnama Aulia Rohma (Proceeding of International Conference on Islamic Boarding School, 2025)
Children’s education based on Qur’anic values plays an important role in forming a generation with noble character and knowledge. Kreatifafa is one of the companies that innovates to develop pop-up children’s books based on the Koran. This company uses technology to convey Islamic teachings creatively so that it can attract children’s interest in understanding Qur’anic values. This research aims to explore the application of QS. al-‘Alaq [96]: 1–5 in the Kreatifafa product, which focuses on the importance of revelation, knowledge and learning as the basis of children’s education. The methodology used in this research is descriptive qualitative with a field method approach, which involves direct observation and interviews with creative product developers and users. The research results show that Kreatifafa has succeeded in integrating Qur’anic values in creative, interactive and educational pop-up book designs. This product proves that students can utilize digital technology to innovate and create products that support Islamic education in the modern era. Apart from that, Kreatifafa is also proof that technology can be an effective da’wah tool for introducing Qur’anic values from an early age in a way that is interesting and easy for children to understand. Thus, Kreatifafa is not just a technology-based product, but is also a real example of successful santripreneurship in responding to the challenges of the times.